Diagnostika subjektivních tĕlesných obtízí. I - Beran, J (Casopis lekaru ceskych, 1989)
The author draw attention to psychological aspects of subjective somatic complaints of neither functional nor organic origin. They stress the role of subjective somatic complaints played in the patient's life. The process of somatization is clarified. It is difficult for the doctor to understand subjective somatic complaints as he is predominantly used to diagnose diseases from the biological viewpoint. The paper gives more detailed characterization of hypochondria using alternative theories to explain it. It also briefly mentions essential characteristics of larvate depression and somatized anxiety.
Keywords: Hypochondriasis; lidé; hypochondrie; Humans